Transformasi Digital dalam Rantai Pasok Agribisnis: Systematic Literature Review Peran Blockchain, IoT, dan Teknologi Digital dalam Meningkatkan Efisiensi, Transparansi, dan Keberlanjutan. - Fauzan Syahrabbani; Mutiara Rinda; Adinda Dwi Kusuma; Intan Nur Aini; Dindy Darmawati Putri; Lutfi Zulkifli (Journal of Agribusiness, Social and Economic, 2026)
Digital transformation is a key factor in addressing low distribution efficiency, limited transparency, and weak tracking systems in Indonesia's agribusiness supply chain. This study aims to analyze the role of digital technologies, specifically blockchain and the Internet of Things (IoT), in improving supply chain management performance. The method used is a Systematic Literature Review (SLR) of 15 relevant journals published between 2015 and 2026. The results indicate that the integration of blockchain and IoT can provide real-time data, enhance product transparency (traceability), and optimize operational efficiency as well as economic and environmental sustainability. However, the implementation of these technologies faces significant challenges, including high investment costs, limited digital infrastructure, and low digital literacy among farmers and MSME actors. Collaboration between stakeholders and government policy support are required to accelerate the adoption of digital technology within the agribusiness ecosystem